Angström-Prescott equation coefficients to Parnaíba, Piaui State, Brazil - Júnior, Aderson Soares de Andrade; Noleto, Donavan Holanda; Silva, Maria Eveline da; Braga, Darlan Leão; Bastos, Edson Alves (Federal University of Piauí, 2012)
The objective of this work was to estimate a and b coefficients of Angström-Prescott equation for Parnaíba, Piaui State, Brazil. Data from 2004 to 2010 of global solar radiation, collected from weather automatic station and data of duration of sunshine, collected from conventional station, were used. The weather automatic station, installed at Embrapa Mid North, belong to INMET network. Angström- Prescott coefficients were determined by linear regression analysis considering rainy (from January to May) and dry (from June to December) season and annual periods. Seasonal coefficients a and b were 0.3107 ± 0.007 and 0.5383 ± 0.012 (rainy season) and 0.3130 ± 0.011 and 0.5086 ± 0.014 (dry season). Annual coefficients a and b were 0.3207 ± 0.006 e 0.4598 ± 0.009, respectively. The seasonal and annual coefficients showed no significant differences. Therefore, the adoption of annual coefficients is recommended.